2010
DOI: 10.1111/j.1447-0756.2010.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative histological study of levels 1-3 supportive tissues using pelvic floor semiserial sections from elderly nulliparous and multiparous women

Abstract: Although all three sites were likely to be injured by delivery, the USCT seemed to be more severely damaged and/or more difficult to be recovered than the ATFP and PM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Using late-stage fetuses, Kato et al [49] demonstrated the female cavernous nerve running through the putative paracolpium. Hirata et al [50] provided a beautiful diagram of the course of the female cavernous nerve covered by the pubocervical fascia, and, later, Hinata et al [19] provided a series of photographs demonstrating the morphology.…”
Section: Methodsmentioning
confidence: 99%
“…Using late-stage fetuses, Kato et al [49] demonstrated the female cavernous nerve running through the putative paracolpium. Hirata et al [50] provided a beautiful diagram of the course of the female cavernous nerve covered by the pubocervical fascia, and, later, Hinata et al [19] provided a series of photographs demonstrating the morphology.…”
Section: Methodsmentioning
confidence: 99%
“…Muscles are not drawn in a dorsal part of the ischorectal fossa (asterisk). In the diagram, the ventral part of the female perineum is drawn according to our recent studies 20,30. ACL, anococcygeal ligament; ATLA, arcus tendineus for the levator ani; BS, bulbospongiosus muscle; CO, coccyx; COM, coccygeus muscle; EAS, external anal sphincter; IC, ishchiocavernosus muscle; LA, levator ani; OI, obturator internus muscle; PB, perneal body; PM, perineal membrane; SSL, sacrospinous ligament; STL, sacrotuberous ligament.…”
Section: Figmentioning
confidence: 99%
“…However, demonstration of both fasciae in a single histological section has been rare: Tamakawa et al [21] did so, but they did not use the common terminology. Hirata et al [11, 30] noted both of the fasciae, but these were beyond the scope of their study. Our present observations of nulliparous women showed that each of the fasciae was independently connected with the superior fascia of the levator ani.…”
Section: Discussionmentioning
confidence: 91%
“…Destruction of the fascial connection is not always evident even in multiparous women, as Hirata et al [11] have demonstrated. Thus, the tendinous arch seemed to be more resistant to vaginal delivery than the uterosacral ligament, which is histologically fragmented in multiparous women [11]. Moreover, in multiparous women, the fascial connection seemed to be replaced by the venous plexus, and the veins were embedded in elastic fiber-rich, loose paravaginal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation